The Inhibitory Effect of Some Benzoic Acid Derivatives on Human Erythrocyte Catalase Activity - Ali, Z.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In order to study the kinetic of human erythrocytes catalase a well –known enzyme uses H2O2 as substrate as well as hydrogen acceptors, in non smokers and smoker individuals. Anthranilic acid and p-Amino Benzoic Acid (PABA) were used to study their effect on the enzyme. The kinetic study confirmed that anthranilic is a non-competitive inhibitor with Km values of 0.95 and 1.0 for non smokers and smokers respectively (PABA) was found to be a competitive inhibitor with Vmax values of 8.0 and 8.9 for nonsmoker and smoker respectively